Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis and Management of Rheumatoid Arthritis - Rudy Hidayat; Bagus Putu Putra Suryana; Linda Kurniaty Wijaya; Anna Ariane; Rakhma Yanti Hellmi; Endy Adnan; Sumariyono (Indonesian Rheumatology Association, 2021)
Introduction: Rheumatoid arthritis (RA) is an autoimmune rheumatic disease which often found in daily practice and requires certain considerations in recognizing clinical appearance also managing the disease as it often causes permanent joint damage, disability, even premature death. This recommendation is expected to become the latest reference for diagnosis and management of RA in Indonesia. Methods: The steering committee was formed by the Indonesian Rheumatology Association (IRA) to formulate key questions; conduct literature search, selection, and review; then formulate recommendation statements for diagnosis, therapy, and monitoring of RA. Furthermore, the steering committee determined the level of evidence and grades of the recommendations. After that, the level of agreement (LOA) was determined for each item by panelists including rheumatology consultants who have been appointed by IRA to represent Indonesia regions. Results: The steering committee established 30 recommendations including diagnosis, the role of laboratory and radiology tests, general treatment, the use of glucocorticoids, sDMARD, bDMARD, and tsDMARD. This recommendation also discusses guidelines on monotherapy, combination therapy, treatment strategies (treat-to-target), tapering, and continuous clinical remission. Treatment on co-morbidities and complications are also included in brief. Conclusion: IRA recommendations regarding the diagnosis and management of RA was made by considering various aspects such as the availability of drugs and supporting facilities, socioeconomic and cultural conditions in Indonesia, as well as the latest research that can be applied to Indonesian population.